2022
DOI: 10.1101/2022.03.29.22273067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of novel nutrient-sensitive gene regulatory networks in amniocytes from fetuses with spina bifida

Abstract: Background: Neural tube defects (NTDs) remain among the most common congenital anomalies. Contributing risk factors include genetics and nutrient deficiencies, however, a comprehensive assessment of nutrient-gene interactions in NTDs is lacking. We hypothesised that multiple nutrient-gene interactions would be evident in NTD-associated gene signatures. Methods: We applied a novel, nutrient-focused gene expression analysis pipeline to identify nutrient-sensitive gene regulatory networks in amniocyte gene expr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The study performed by Wang et al showed that SOX11 is essential for both embryonic and adult neurogenesis, by transient proliferation deficits in neural progenitor cell proliferation [ 46 , 47 ]. Moreover, QSOX1 has been associated with neural tube defect development via its interaction with valproic acid and folic acid [ 12 ]. The potentially disturbed function of genes indicated by DE miRNAs suggests involvement in the processes of neurogenesis, responses to oxidative stress, lipid metabolism, and the transport and distribution of folic acid, which confirms the complex pathogenesis of developmental defects in SB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study performed by Wang et al showed that SOX11 is essential for both embryonic and adult neurogenesis, by transient proliferation deficits in neural progenitor cell proliferation [ 46 , 47 ]. Moreover, QSOX1 has been associated with neural tube defect development via its interaction with valproic acid and folic acid [ 12 ]. The potentially disturbed function of genes indicated by DE miRNAs suggests involvement in the processes of neurogenesis, responses to oxidative stress, lipid metabolism, and the transport and distribution of folic acid, which confirms the complex pathogenesis of developmental defects in SB.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, introducing miRNA expression patterns to the diagnostic protocol may improve SB detection and also aid personalized clinical management [ 10 ]. Since the pathogenesis of SB is still unknown, the comprehensive knowledge of SB development may introduce new treatment targets, improve surgical techniques, and enhance the prognosis for neonates [ 11 , 12 , 13 ]. Thus, the main objective of the current study was to evaluate the significance of miRNAs in the pathogenesis of SB.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether patterns of differential gene expression in cases differed according to placental location, DEGs with known cell-specific expression at the maternal-fetal interface were also identified (expression threshold ≥ 1; PlacentaCellEnrich) and characterized according to known expression patterns in the placenta 227,228 . Lastly, to determine the extent to which DEGs in cases are sensitive to, or interact with, nutrients, DEGs that coded for micronutrient-dependent proteins (i.e., proteins with ≥1 micronutrient cofactor) were identified and used to construct DEG-nutrient interaction networks 229,230 .…”
Section: Rna Extraction and Expression Profilingmentioning
confidence: 99%